Thermodynamic analysis of 6xxx series Al alloys: phase fraction diagrams (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Microstructural evolution of 6xxx Al alloys during various metallurgical processes was analyzed using accurate and comprehensive thermodynamic database. Phase fractions of all the possible precipitate phases which can form in the as-cast and equilibrium status of the Al-Mg-Si-Cu-Fe-Mn-Cr alloys were calculated over the technically useful composition range. The influences of minor elements such as Cu, Fe, Mn, and Cr on the amount of each type of precipitates in the as-cast and equilibrium conditions were analyzed. Phase fraction diagrams at 500 °C were mapped in the composition range of 0-1.1 wt.% Mg and 0-0.7 wt.% Si to investigate the as-homogenized microstructure. In addition, phase fraction diagram of Mg2Si at 177 °C was mapped to understand the microstructure after final annealing of 6xxx Al alloy. Based on the calculated diagrams, the design strategy of 6xxx Al alloy to produce highest strength was discussed.